2017
DOI: 10.1128/msystems.00169-16
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Gut Metabolites and Microbial Composition and Functions between Egyptian and U.S. Children Are Consistent with Their Diets

Abstract: The human gastrointestinal microbiota functions as an important mediator of diet for host metabolism. To evaluate how consumed diets influence the gut environment, we carried out simultaneous interrogations of distal gut microbiota and metabolites in samples from healthy children in Egypt and the United States. While Egyptian children consumed a Mediterranean diet rich in plant foods, U.S. children consumed a Western diet high in animal protein, fats, and highly processed carbohydrates. Consistent with the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 89 publications
5
130
3
Order By: Relevance
“…To illustrate the advantage of phylogenetic distance based constrained ordination in microbial ecology, we extended the use of a distance-based variant of redundancy analysis (dbRDA) 13, 14 to utilize the phylogenetic UniFrac (UF) distance-based matrix of (dis)similarities among samples in a dataset as has been done in several previous studies 15–18 . UniFrac distance is computed by calculating the fraction of branch lengths of a combined phylogenetic tree that are not shared between two communities 19 .…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate the advantage of phylogenetic distance based constrained ordination in microbial ecology, we extended the use of a distance-based variant of redundancy analysis (dbRDA) 13, 14 to utilize the phylogenetic UniFrac (UF) distance-based matrix of (dis)similarities among samples in a dataset as has been done in several previous studies 15–18 . UniFrac distance is computed by calculating the fraction of branch lengths of a combined phylogenetic tree that are not shared between two communities 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Mitsuokella, like Treponema, showed significant differential abundance only in the lean Bushbuckridge group. Although not a benchmarked traditional taxon, Mitsuokella has repeatedly been associated with non-Western diets and lifestyles 48,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite not reaching statistical significance when compared to benchmarked datasets, the large Several studies have identified obesity-associated taxa primarily in non-African populations 23,48,49 despite these reported connections being inconsistent 1,21,2,67 . The differential abundance, prevalence or presence of microbial taxa across populations may require population-specific associations for relevance as universal classifications may not necessarily be generalizable.…”
Section: Algerian Tuaregs Saudi Bedouins and Amazonians From Frenchmentioning
confidence: 99%
See 1 more Smart Citation
“…This has broad application across biomedical and environmental science, and in particular, allows for detection of changes in communities or the genes that they carry in the face of biological (Marti et al 2017), chemical (Chambers et al 2015) or environmental (Garner et al 2016) factors. Of particular relevance are studies on antimicrobial resistance (Zhu et al 2013;Su et al 2015;Chambers et al 2015;Chen et al 2016;Garner et al 2016), as well as studies in other areas, such as changes in gut flora in different human communities (Shankar et al 2017) or through the ingestion of probiotics (Unno et al 2015).…”
Section: Introductionmentioning
confidence: 99%